Plasma Asprosin Concentrations Are Increased in Individuals with Glucose Dysregulation and Correlated with Insulin Resistance and First-Phase Insulin Secretion. (20th March 2018) - Wang, Yuren; Qu, Hua; Xiong, Xin; Qiu, Yuyang; Liao, Yong; Chen, Yingchun; Zheng, Yi; Zheng, Hongting
Abstract : Background . Adipokines are reported to participate in many common pathologic processes of glucose dysregulation, such as insulin resistance, β -cell dysfunction, and chronic inflammation. Objective . To detect the concentrations of plasma asprosin in subjects with impaired glucose regulation (IGR) and newly diagnosed type 2 diabetes (nT2DM) and its relationship to parameters of glucose and lipid metabolism, insulin resistance, and pancreatic β -cell function. Methods . 143 eligible participants were included and were divided into three groups including normal glucose regulation (NGR, n = 52 ), IGR (n = 40 ), and nT2DM group (n = 51 ). The intravenous glucose tolerance test (IVGTT) and clinical and biochemical parameters were measured in all participants. Results . Plasma asprosin levels were higher in IGR (82.40 ± 91.06 ng/mL, P < 0.001 ) and nT2DM (73.25 ± 91.69 ng/mL, P < 0.001 ) groups compared with those in the NGR (16.22 ± 9.27 ng/mL) group, especially in IGR subjects. Correlation analysis showed that plasma asprosin levels were positively correlated with waist circumference (Wc), fasting plasma glucose (FPG), postchallenge plasma glucose (2hPG), HbA1c, triglyceride (TG), and homeostasis model assessment for insulin resistance (HOMA-IR) and negatively correlated with homeostasis model assessment for β -cell function (HOMA- β ), area under the curve of the first-phase (0–10 min) insulin secretion (AUC), acute insulin response (AIR), and glucose disposition index (GDI) (allP < 0.05 ). Multiple logistical regression analyses revealed that plasma asprosin concentrations were significantly correlated with IGR and nT2DM after controlling for age, sex, BMI, and WHR. Conclusions . Circulating asprosin might be a predictor of early diagnosis in DM and might be a potential therapeutic target for prediabetes and T2DM.